한국잔디 신품종 ‘남부1’ 개발 - 배은지(Eun-Ji Bae); 이광수(Kwang-Soo Lee); 윤준혁(Jun-Hyuck Yoon); 전권석(Kwon-Seok Jeon) (Weed & turfgrass science, 2023)
2010년도 국내 남·동해안 및 서해안, 도서, 내륙지역에서 zoysiagrass 159개체를 수집하였다. 수집된잔디유전자원은 유전자원포장에 이식을 하여 2011년~2013년 3년간 포장조사를 실시하여 형태적으로 구별성, 안정성을 확인하였고, 생육이 우수하고, 밀도가 높은 ’남부1’을 선발하였다. ’남부1’의 초장과 엽장은 12.8과 10.9 ㎝로 ’들잔디’와 ’제니스’와 유사한 특성을 보였으나, 엽폭은 3.5 ㎜로 중엽형으로 ’들잔디’와 ’제니스’에 비해 좁은특성을 나타내었다. 최하위 잎의 높이는 1.6 ㎝ 로 ’들잔디’에 비해 낮게 자라며, 포복경 길이는 39.5 ㎝로 길었고, 생육이 왕성한 특성을 갖고 있다. 봄철그린업은 ’들잔디’와 ’제니스’와 유사하게 3월 중순부터 잎이 나오기 시작하여그린업속도가 빨랐다. 다른 종들에 비해 왕성한 포복·지하경형 생장 특성을 가졌으며, ’들잔디’에 비해 확연히 지면피복도가 높은 특성을 보였다. In 2010, 159 of native zoysiagrasses were collected from the south, east, west coasts, islands, and inland regions of Korea. The collected grass genetic resources were transplanted into the genetic resource field. Field research was conducted for three years, from 2011 to 2013, to confirm morphological differentiation and stability, and then ‘Namboo1’ with excellent growth and high density was selected. The plant height and leaf length of 'Namboo1' were 12.8 and 10.9 cm, showing similar characteristics to Zoysia japonica and 'Zenith,' However, the leaf width was 3.5 mm, mid-leaf, narrower than that of Z. japonica and 'Zenith.' The height of the lowest leaf was 1.6 cm, lower than Z. japonica, and the length of the stolon was 39.5 cm, with vigorous growing characteristics. Like Z. japonica and ‘Zenith,’ the spring greenup started in mid-March and continued at high speed. Compared to other species in terms of density, it had the characteristics of a stoloniferous/rhizomatous-type growth habit, and the ground cover was higher than that of Z. japonica. KCI Citation Count: 0